The effect of different dietary and therapeutic solutions on the color stability of resin-matrix composites used in dentistry: An in vitro study - Lopes-Rocha, L (2021)
The purpose of this study was to evaluate the color stability of aesthetic restorative resin-matrix materials after their immersion in different dietary and therapeutic solutions. Thirty disc-shaped specimens (10 × 2 mm) were prepared from three different types of resin-matrix composites used in dentistry (BE, FS, AF). The color coordinates (L*a*b*, ¿L*, ¿a*, ¿a*, ¿b* and ¿E*) were measured using a VITA Easyshade 3D-Master (VITA Zahnfabrik, Bad Säckingen, Germany) before and after the immersion of the specimens in coffee, red wine, Coca-Cola®, Eludril Care®, and distilled water solutions for 40 h. The color change (¿E*) was calculated and analyzed by the Kolmogorov-Smirnov test and the Kruskal-Wallis multiple-comparison test. All the restorative materials showed significant color (¿E*) changes after their exposure to red wine, followed by coffee and Coca-Cola®; however, one nanohybrid resin-matrix composite showed a high color stability in such colored test solutions. The chemical composition and content of the organic matrix played a key role in the color stability of the resin-matrix composites. Clinicians should advise their patients about the chemical interaction between dietary substances and different resin-matrix composites.